Caesarean section and gut microbiota in children - Ariani Dewi Widodo; Mohammad Juffrie (World Nutrition Journal, 2020)
Over the last two decades, the C-section rate has increased worldwide. It is understood that colonization patterns of intestinal microbiota in infant delivery in C-section vary from those that were delivered vaginally. These different microbial pattern and diversity will impact and respond to immune and dysbiosis-related diseases. This article examined the effect of C-section on gut microbiota in children.Recent Findings: Newborns are influenced by various factors, including mode of delivery, feeding, nutrition, hospitalization, antibiotic and host gene. Several studies have shown that infants with C-section have lower Bifidobacterium while others have shown lower abundance of Enterobactericeae and Bacteroides in infants with C-section compared to infants born vaginally. Although the mode of delivery is only one factor that influences infant microbiota composition, studies conclude that reduced microbial exposure during the C-section is important because it can affect dysbiosis several years after birth. Good microbiota is a key source of microbial-driven immune regulation, changes in normal patterns of bacterial colonization can alter the immune development outcome and may predispose to certain immune-related disorders later in life.Summary: The composition and concentrations of intestinal microbiota between vaginally and C-section born infants are significantly different. Among C-section infants, gut microbiota is associated with lower diversity and therefore induces dysbiosis, which can affect immune development and may predispose to some immune disorders, i.e. allergies in particular. Nutritional approach with pre-, probiotics, and/or synbiotics can have a promising effect early in life in preventing gut dysbiosis.